2023
DOI: 10.1007/s10460-023-10451-5
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of conservation practices in the Corn Belt: the role of one formal farmer network, Practical Farmers of Iowa

Abstract: Substantial evidence has shown that involvement in peer-to-peer farming networks influences whether a farmer decides to try a new practice. Formally organized farmer networks are emerging as a unique entity that blend the benefits of decentralized exchange of farmer knowledge within the structure of an organization providing a variety of sources of information and forms of engagement. We define formal farmer networks as farmer networks with a distinct membership and organizational structure, leadership that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In the U.S., farmer and community-level innovation is the main pathway for transitions to diversified farming systems because policies and markets that promote diversification are limited [23,24]. Here, we focused on a federal conservation program that could help alleviate the large structural constraints to cover cropping.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., farmer and community-level innovation is the main pathway for transitions to diversified farming systems because policies and markets that promote diversification are limited [23,24]. Here, we focused on a federal conservation program that could help alleviate the large structural constraints to cover cropping.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…the Farm Bill), concentrated markets, and corporate power that work in concert to disproportionately support simplified cropping systems [23]. Adoption of conservation practices therefore typically occurs through grassroots networks that emphasize peer-to-peer learning [24]. A large body of research has focused on behavioral and demographic factors that influence practice adoption, while structural factors, including agri-environmental policies, are understudied [20,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…Implicit in these efforts is the premise that increasing the adoption of diversified farming systems at a regional scale requires weaving together a multiplicity of different place-based projects. Doing so is likely to require organizing farmer networks and cross-sector community support (Asprooth et al, 2023).…”
Section: Advancing Regional Diversification: Vital Roles For Integrat...mentioning
confidence: 99%
“…Nazu S B et al's (2022) [4] study on the willingness to pay for adopting conservation tillage in terms of individual and co-operative payment systems of wheat farmers in Bangladesh found that co-operatives formed based on farmers' WTP can promote the adoption of conservation tillage by reducing the cost of conservation tillage for farmers. L. Asprooth, M. Norton, and R. Galt (2023) [21] researched how participation and forms of engagement in the farmer network of the formal organization Practical Farmers of Iowa (PFI) are associated with the adoption of conservation practices. L. Asprooth, M. Norton, and R. Galt (2023) [21] found that PFI supports farmers in adopting conservation tillage technologies by providing information, resources, encouragement, confidence building, and reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…L. Asprooth, M. Norton, and R. Galt (2023) [21] researched how participation and forms of engagement in the farmer network of the formal organization Practical Farmers of Iowa (PFI) are associated with the adoption of conservation practices. L. Asprooth, M. Norton, and R. Galt (2023) [21] found that PFI supports farmers in adopting conservation tillage technologies by providing information, resources, encouragement, confidence building, and reinforcement. Formal networks in PFI, which build relationships by providing face-to-face learning opportunities, are essential for conservation tillage promotion.…”
Section: Introductionmentioning
confidence: 99%